Patients newly diagnosed with ulcerative colitis receive earlier treatment in surgical clinics. (30th July 2013) - Ward, S. T.; Li, K. K.; Trivedi, P. J.; Hejmadi, R. K.; Suggett, N.; Iqbal, T.; Ismail, T.
Abstract: Aim: The diagnosis and treatment of ulcerative colitis (UC) is traditionally the realm of gastroenterologists. However, the symptoms of UC overlap with those of bowel cancer and patients may be initially referred to colorectal surgery clinics. The aims of this study were to define which specialty most frequently diagnoses UC and to determine if there were differences in management between the two specialities. Method: The demographics, presenting symptoms and clinical management of patients with newly diagnosed UC were determined and compared by speciality clinic of initial referral. Histopathology reports and clinic letters were reviewed to identify patients newly diagnosed with UC at a large university teaching hospital from January 2007 to January 2012. Results: Patients were more commonly referred to colorectal surgeons (74 vs 41 patients) than gastroenterologists. Patients referred to gastroenterology were younger (36.0 vs 59.6 years, P < 0.01) but there were no significant differences in gender, presenting symptoms or disease extent. Rigid sigmoidoscopy ± biopsy was more commonly performed in colorectal clinic (93.2 vs 31.7%, P < 0.01). There was a significantly shorter delay in starting disease‐specific treatment for those patients referred initially to colorectal surgery (13.8 vs 33.6 days, P = 0.01). Performing rigid sigmoidoscopy in clinic was associated with starting disease‐specific treatment at this visit. Conclusion: Patients with first presentation UC are more commonly seen in colorectal surgery clinics where rigid sigmoidoscopy is more frequently undertaken, allowing earlier commencement of UC treatment.